Business Process Engineering bagi Pengembangan Desa Wisata Berkelanjutan pada obyek wisata Pulo Sigeni, Padukuhan Kisik, Desa Sendangagung, Kabupaten Sleman - Ilsa Haruti Suryandari; Rubiyatno -; F A Joko Siswanto; Gisilowati Dian Purnamasari; Klemensia Erna Christina Sinaga (Jurnal Publika Pengabdian Masyarakat, 2020)
The community service program aims to assist Pulo Sigeni tourism site to have structured management. Further, it will create accountable dan transparent governance to achieve sustainable tourism destination. Methods used in this program were field observation, training, simulation, and focus group discussion. Constructed and documented recommendation of business process is the result of this project. Hence, this recommendation is expected to be a guidance for tourism operator to operate business activities in this location which give benefit in community empowerment as well as establish environmentally friendly tourism destination. Keywords— Business Process Engineering, tourism destination, sustainable